Cardiac dysfunction in medulloblastoma survivors treated with photon irradiation. Issue 4 (23rd April 2022) - Cacciotti, Chantel; Chordas, Christine; Valentino, Katie; Allen, Rudy; Lenzen, Alicia; Burns, Karen; Nagarajan, Rajaram; Manley, Peter; Pillay-Smiley, Natasha
Abstract: Background: Medulloblastoma is an aggressive central nervous system (CNS) tumor that occurs mostly in the pediatric population. Treatment often includes a combination of surgical resection, craniospinal irradiation (CSI), and chemotherapy. Children who receive standard photon CSI are at risk for cardiac toxicities including coronary artery disease, left ventricular scarring and dysfunction, valvular damage, and atherosclerosis. Current survivorship guidelines recommend routine echocardiogram (ECHO) surveillance. In this multi-institutional study, we describe markers of cardiac dysfunction in medulloblastoma survivors. Methods: A retrospective chart review of medulloblastoma patients who had photon beam CSI was followed by ECHO between 1980 and 2010 at Lurie Children's Hospital and Dana-Farber/Boston Children's Hospital. Results: During the 30-year study period, 168 medulloblastoma patient records were identified. Included in this study were the 75 patients who received CSI or spinal radiation and ECHO follow-up. The mean age at CSI was 8.6 years (range, 2.9-20), and the mean number of years between radiation therapy (RT) completion and first ECHO was 7.4 (range, 2-16). Mean ejection fraction (EF) was 60.0% and shortening fraction (SF) was 33.8%. Five patients (7%) had abnormal ECHO results: three with EF <50% and two with SF <28%. Conclusion: The majority of medulloblastoma patients who received CSI have relatively normal ECHOs post-treatment; however, 7% of patients had abnormal ECHOs. The implication of our study for medulloblastoma survivors is that further investigations are needed in this population with a more systematic, longitudinal assessment to determine predictors and screenings.